ENERGY TRANSITION AND TOURISM PROSPECTS IN INDONESIA - Istiadi, Istiadi (UI Scholars Hub, 2022)
The Energy Transition is an effort to shift the use of fossil-based energy to non-fossil energy. Fossil-based energy is proven to cause pollution to the human environment. Meanwhile, non-fossil energy does not only have a positive impact on natural life so that it can have an impact on the tourism aspects of a region or country. This paper attempts to describe how the energy transition process is carried out and its relation to tourism in a region. The type of research carried out is qualitative research which originates from various secondary data both in the general media and in certain journals. As a result, clean and healthy air conditions will have a positive impact on the world of tourism in general